2018
DOI: 10.3892/etm.2018.6947
|View full text |Cite
|
Sign up to set email alerts
|

3D printed poly(ε‑caprolactone) scaffolds function with simvastatin‑loaded poly(lactic‑co‑glycolic acid) microspheres to repair load‑bearing segmental bone defects

Abstract: Repairing critical-sized bone defects has been a major challenge for orthopedic surgeons in the clinic. The generation of functioning bone tissue scaffolds using osteogenic induction factors is a promising method to facilitate bone healing. In the present study, three-dimensional (3D) printing of a poly(lactic-co-glycolic acid) (PLGA) scaffold with simvastatin (SIM) release functioning was generated by rapid prototyping, which was incorporated with collagen for surface activation, and was finally mixed with SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Together, these results suggest that the scaffold composition, cytocompatibility, and capacity to be integrated by the surrounding tissues may play a key role in the IM bone healing process. No doubt, recent advances in biodegradable cellular scaffolds will be of particular interest to test in the Masquelet technique in animal models (Encarnação et al, 2019;Zhang, Zhang, & Zhang, 2019).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Together, these results suggest that the scaffold composition, cytocompatibility, and capacity to be integrated by the surrounding tissues may play a key role in the IM bone healing process. No doubt, recent advances in biodegradable cellular scaffolds will be of particular interest to test in the Masquelet technique in animal models (Encarnação et al, 2019;Zhang, Zhang, & Zhang, 2019).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In the absence of nHA or GO, pure aliphatic polyester scaffolds must be seeded with bioactive molecules or growth factors followed by implanting into bone defects of animal models. For instance, Zhang et al loaded simvastatin (SIM) into 3D PLGA scaffolds fabricated by the FDM process; collagen was also incorporated into the scaffolds for surface activation [273]. They reported that such PLGA/Col/SIM scaffolds can induce new bone formation at the defects created at the femurs of Sprague-Dawley rats.…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%
“…The new bone formation was more evident in CH-Ca-SV, with various mineralization foci being detected not only at the borders but also inside the scaffold structure. The potential of SV as a biological cue in cell-homing strategies has been demonstrated by previous in vivo studies in which SV-loaded scaffolds improved critical-size bone defect regeneration as well as hastened the fracture-healing and union process (Xue et al 2019; Zhang et al 2019; Hajializade et al 2020). Researchers have found that SV acts as an activator to enhance the regeneration of bone defects along with hydroxyapatite ceramics in different scaffold formulations (Wang et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Another strategy to improve and fasten neo-tissue-genesis is to incorporate a bioactive cue on scaffold composition. Local simvastatin (SV) delivery is a strategy successfully used to increase and anchor bone regeneration by creating scaffolds capable of releasing bioactive dosages of this drug at the application site (Li et al 2018; Wang et al 2018; Xue et al 2019; Zhang et al 2019; Hajializade et al 2020). Chitosan has been considered a suitable carrier system for poorly soluble drugs, such as SV, increasing its solubility and thereby its bioavailability for several clinical applications (Selvasudha and Koumaravelou 2017).…”
Section: Introductionmentioning
confidence: 99%